Wrist injuries in tennis players: A narrative review - Stuelcken, M.; Mellifont, D.; Gorman, A.; Sayers, M. (Sports Medicine, 2017)
The wrist/hand complex forms the crucial final link in the kinetic chain between the body and the racquet and therefore has a number of important roles in the production of all tennis strokes. However, the internal and external loads that are created at the wrist during these strokes have the potential to contribute to pain and injury. Therefore, the purposes of this narrative review are to (1) determine the extent of the problem of wrist pain/injury in tennis players, (2) identify bony and soft tissue structures of the wrist that are susceptible to damage as a result of tennis play and (3) explore factors that may influence the development of wrist pain/injury in tennis players. The epidemiological data revealed two important points. First, some evidence suggests wrist pain/injury accounts for a higher percentage of total injuries in more recent studies (2014-2015) than in early studies (1986-1995). Second, the relative frequency of wrist pain/injury compared with other well-recognized problem areas for tennis players such as the shoulder complex, elbow and lumbar spine is noticeably higher in more recent studies (2014-2015) than in early studies (1986-1995), particularly among females. Collectively, this would seem to indicate that the problem of wrist pain/injury has increased in the modern game. In fact, some wrist injuries appear to be related to the use of certain forehand grip types and the predominant use of the two-handed backhand. While the loads experienced at the wrist during tennis stroke production seem to be below threshold levels for a single event, the cumulative effects of these loads through repetition would appear to be an important consideration, especially when inadequate time is allowed to complete normal processes of repair and adaptation. This is supported by the evidence that most wrist injuries in tennis are associated with overuse and a chronic time course. The complex interaction between load, repetition, and training practices in tennis, particularly among young developing players who choose a path of early specialization, needs to be further explored.